Early survival in Atlantic salmon is associated with parental genotypes at loci linked to timing of maturation - Aykanat, Tutku; McLennan, Darryl; Metcalfe, Neil B; Prokkola, Jenni M (Oxford University Press, 2024)
Large effect loci often contain genes with critical developmental functions and potentially broad effects across life stages. However, their life stage-specific fitness consequences are rarely explored. In Atlantic salmon, variation in two large-effect loci, six6 and vgll3, is linked to age at maturity and several physiological and behavioral traits in early life. By genotyping the progeny of wild Atlantic salmon that were planted into natural streams with nutrient manipulations, we tested if genetic variation in these loci is associated with survival in early life. We found that higher early-life survival was linked to the genotype associated with late maturation in the vgll3, but with early maturation in the six6 locus. These effects were significant in high nutrients but not in low-nutrient streams. The differences in early survival were not explained by additive genetic effects in the offspring generation but by maternal genotypes in the six6 locus and by both parents’ genotypes in the vgll3 locus. Our results suggest that indirect genetic effects of large-effect loci can be significant determinants of offspring fitness. This study demonstrates an intriguing case of how large-effect loci can exhibit complex fitness associations across life stages in the wild and indicates that predicting evolutionary dynamics is difficult.
Keywords: age at maturity; indirect genetic effects; parental fitness effect; vgll3; six6; Atlantic salmon